Strengthening Criminal Law Enforcement Against Forest and Land Fires Based on Sustainable Development Goals to Realize Sustainable Environmental Protection - Tricho Dike Fierrera; Sunardi Sunardi; Zainal Arifin Hoesein (International Journal of Sociology and Law, 2026)
Forest and land fires remain a major environmental challenge in Indonesia, causing significant impacts on ecosystems, public health, the economy, and sustainable development. Although various regulations, including Law Number 41 of 1999, Law Number 32 of 2009, and Law Number 18 of 2013, have been enacted, recurring fires indicate that the primary issue lies in the effectiveness of criminal law enforcement rather than the absence of legal instruments. This study aims to analyze the effectiveness of criminal law enforcement against forest and land fires and formulate strategies to strengthen enforcement based on the Sustainable Development Goals (SDGs). The research employs a normative juridical method using statutory, conceptual, and case approaches through the analysis of relevant legislation and court decisions. The findings reveal that law enforcement remains constrained by weak supervision, difficulties in proving environmental crimes, limited inter-agency coordination, and ineffective corporate criminal liability. Strengthening enforcement requires regulatory harmonization, improved use of science- and technology-based evidence, stronger institutional coordination, and integration of sustainable development principles into law enforcement policies. These measures are expected to enhance environmental protection, deter offenders, and support the achievement of the SDGs, particularly in ecosystem conservation, climate action, and institutional accountability.